2008
DOI: 10.1177/0256090920080404
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Mobile Advertising: The Indian Scenario

Abstract: includes research articles that focus on the analysis and resolution of managerial and academic issues based on analytical and empirical or case research KEY WORDS Consumer ResponsivenessMobile AdvertisingPurchase Decision Customization CustomerizationIn the current scenario, mobile internet applications enable consumers to access a variety of services: Web information search, SMS (short message service), MMS (multimedia message service), banking, payment, gaming, e-mailing, chat, weather forecast, GPS (global… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 17 publications
1
21
1
1
Order By: Relevance
“…Consumers with lack of experience also found to rely heavily on the opinion of reference groups to engage (Mowen & Minor, 2001;Triandis, 1971Triandis, , 1979Zhang & Mao, 2008) or to reduce uncertainty upon adopting a particular innovation (Baron & Byrne, 2000;Muk & Babin, 2006). Parallel to the suggestion made by Ajzen (1991) and Davis, et al (1989), Tripathi and Siddiqui (2008) and Bagozzi, et al (2000) reiterated that consumers' socio-cultural environment (i.e. family, informal sources, culture and sub-culture) which is also similar to the subjective norm found to have a significant impact on their purchase decision.…”
Section: Review Of Literaturesmentioning
confidence: 84%
See 2 more Smart Citations
“…Consumers with lack of experience also found to rely heavily on the opinion of reference groups to engage (Mowen & Minor, 2001;Triandis, 1971Triandis, , 1979Zhang & Mao, 2008) or to reduce uncertainty upon adopting a particular innovation (Baron & Byrne, 2000;Muk & Babin, 2006). Parallel to the suggestion made by Ajzen (1991) and Davis, et al (1989), Tripathi and Siddiqui (2008) and Bagozzi, et al (2000) reiterated that consumers' socio-cultural environment (i.e. family, informal sources, culture and sub-culture) which is also similar to the subjective norm found to have a significant impact on their purchase decision.…”
Section: Review Of Literaturesmentioning
confidence: 84%
“…Meanwhile, voluntary means the opportunity given to consumers for them to decide whether to participate or not to participate with a particular innovation (Ajzen, 1991;Bamba & Barnes, 2007;Kim, et al, 2010;Yang, 2007). Prior literatures revealed that consumers' ability on behavioral control has a significant positive influence on many behavioral intentions (Bauer, et al, 2005;Carroll, et al, 2007;Hongwei, et al, 2010;Leppaniemi & Karjaluoto, 2005;Merisavo, et al, 2010;NOKIA, 2002;Nysveen, et al, 2005;Sheppard, Hartwick, & Warshaw, 1988;Tripathi & Siddiqui, 2008;Tsang, et al, 2004;Venkatesh, et al, 2003). In fact, studies in developed countries disclosed that many consumers appreciate rights to have behavioral control (Hongwei, et al, 2010;Leppaniemi & Karjaluoto, 2005;Okazaki, et al, 2009).…”
Section: Review Of Literaturesmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Intrusiveness has been viewed as one of main causes for ad avoidance 29,30 together with irritation, with both affecting attitude towards the ad 31 and eventually behaviour, to read the ad or delete it. 32 It seems the perception of intrusiveness is somehow moderated by the level of personalisation of the offer and the situation: the more the mobile ad offer is seen as of interest to individuals, the less intrusive it is perceived 33 ; and the more an individual is in a state of idleness, the less intrusive it is perceived to be. …”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…43 Furthermore, incentives can be critical in a mobile environment where SMS ads are perceived as intrusive by nature. To the extent that consumers perceive mobile ads as relevant to them 32,33 and of value, 22,44 the less intrusive the SMS ad could be perceived.…”
Section: 4041mentioning
confidence: 99%